Determinación del comportamiento del suelo por medio de fotogrametría, en la zona norte de Cartago, relacionando propiedades mecánicas del suelo y precipitación - Aguilar-Martínez, Andrey Esteban (Instituto Tecnológico de Costa Rica, 2018)
Agriculture is the economic activity with the greatest impact on the population of the northern zone of the province of Cartago. Hundreds of farmers grow their land year after year in a very accelerated way to supply the entire national territory, due to this there is a large wear of the land that in turn is generally worked through mechanization with tractors, including terrains with steep slopes, which are highly prone to water erosion. The main objective of this project is to determine the behavior at ground level by means of photogrammetry through time with the cultivation of potatoes (Solanum tuberosum). Penetration resistance tests, bulk density sampling, drone flights and field measurements were performed to verify level variations in the soil by means of photogrammetry due to water erosion or rearrangement of soil particles, and the precipitation of the area as a possible factor in the movement of the soil. From the methodology carried out, different results were obtained, among them: the resistance to penetration is lower when machining with spade machine and there is a lower rate of soil loss, it is possible to detect by means of photogrammetry the measurement of the level change of the surface of the ground; however, they are high data that do not really correspond to the reality of the terrain. As the precipitation increases, so does the loss of soil, even the erosion rate is higher in mechanized lands with chisel plows, reaching a value of 5,841 ton/ha in this project. It is recommended to continue doing research of this type, by universities and professionals, as it is a good for the academic and economic sector of Costa Rica.
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018.
Keywords: Suelos; Fotogrametría; Precipitación; Agricultura; Cultivos; Erosión